Landscape composition regulates the spillover of beneficial insects between forest remnants and adjacent coffee plantations - Reis Medeiros, Hugo [UNESP]; Martello, Felipe; Metzger, Jean Paul; Harper, Karen Amanda; Mengual, Ximo; Righi, Ciro Abbud; Ribeiro, Milton Cezar [UNESP] (Elsevier, 2021)
Cross-habitat movements are crucial for persistence of beneficial insects in agricultural landscapes; however, much remains unknown on how landscape structure affects the spillover of beneficial insects between crop and non-crop habitats. To estimate the effects of landscape structure on the spillover of beneficial insects we sampled predatory wasps in pairs of forest remnants and adjacent coffee plantations along a gradient of landscape composition and configuration. We used dissimilarity indices to estimate wasp spillover and we assumed that high dissimilarity means less flow (and thus less spillover) between forest and coffee habitats. We collected a total of 9847 wasps classified into 75 species and 23 genera. Wasp dissimilarity between habitats decreased with increasing forest cover in the surrounding landscape and did not respond to landscape diversity, edge density or pesticide usage. Our findings suggest that wasps forage in coffee plantations but seem to rely on forest remnants to find unmanaged nesting sites and a constant supply of resources that are not available in the agricultural matrix, and are neither in landscapes with high compositional diversity or edge density. Therefore, forest conservation and restoration should be incorporated in agro-environmental schemes designed to improve the spillover of beneficial insects and provision of ecosystem services within coffee farmlands.
Keywords: Agricultural landscapes; Forest conservation; Habitat amount; Inter-patch movement; Nesting habitats; Predatory wasps